2016
DOI: 10.1002/joc.4657
|View full text |Cite
|
Sign up to set email alerts
|

Heat, water and carbon exchanges in the tall megacity of Shanghai: challenges and results

Abstract: The observed surface energy balance fluxes are essential to improve model forecasting ability but such data are scarce for subtropical cities and urban areas with tall buildings. One year of eddy covariance flux data for an area within Shanghai with a wide range of building heights (8-150 m, mean by direction) are analysed by wind direction. Consideration is given to how to distinguish between local-and micro-scale fluxes. At the local-scale, median daily peaks of sensible heat flux occur in the early afternoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 70 publications
4
43
1
Order By: Relevance
“…The higher IAP Q res / Q * is indicative of both larger heat storage associated with the tall buildings (Miao et al, ) but with relatively open spacing. These values are comparable with the COSMO (Comprehensive Outdoor Scale Model experiments, Tokyo) site (Kawai and Kanda, ) and Shanghai (Ao et al, ), with similarly large building and impervious fractions. In such settings, there is a large area of exposed walls that can heat up (cool down) and a large canopy layer volume.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The higher IAP Q res / Q * is indicative of both larger heat storage associated with the tall buildings (Miao et al, ) but with relatively open spacing. These values are comparable with the COSMO (Comprehensive Outdoor Scale Model experiments, Tokyo) site (Kawai and Kanda, ) and Shanghai (Ao et al, ), with similarly large building and impervious fractions. In such settings, there is a large area of exposed walls that can heat up (cool down) and a large canopy layer volume.…”
Section: Resultssupporting
confidence: 88%
“…Previous urban studies have reported both positive and negative nocturnal Q H fluxes (Christen and Vogt, ; Grimmond et al, ; Offerle et al, ; Goldbach and Kuttler, ; Kotthaus and Grimmond, ; Ao et al, ). At less built up suburban sites, Q H values are, generally, negative at night as a result greater surface cooling (Grimmond and Oke, ; Christen and Vogt, ; Offerle et al, ; Newton et al, ; Balogun et al, ; Goldbach and Kuttler, ; Ward et al, ; Oke et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some short‐term observations (usually biased towards dry conditions) are available from Mexico City (Oke et al , , ; Tejeda‐Martinez and Jauregui, ; Velasco et al , ), Ouagadougou (Offerle et al , ), Miami (Newton et al , ) and Cairo (Frey et al , ). However, there is a significant lack of long‐term campaigns, which have only been conducted over residential areas in Phoenix (Chow et al , ), Singapore and Mexico City with initial results recently published as part of carbon sequestration research (Velasco et al , ) and a densely built‐up commercial site in Shanghai (Ao et al , ). A few generalizations nevertheless follow from the mostly suburban (sub)tropical work as summarized in Roth ().…”
Section: Introductionmentioning
confidence: 99%
“…Residual: practical difficulties of direct measurement of Q S in urban areas, result in the SEB residual (i.e. Q * +Q F −(Q H + Q E )) frequently being the "preferred" observations (Ao et al, 2016;Ching et al, 1983;Doll et al, 1985;Li et al, 2015;Oke and Cleugh, 1987) (where Q F is the anthropogenic heat flux).…”
Section: Introductionmentioning
confidence: 99%